2012
DOI: 10.1111/j.1532-5415.2012.03928.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tai Chi as a Community‐Based Falls Prevention Intervention: A Randomized Controlled Trial

Abstract: There was no difference in falls rates between the groups, with falls reducing similarly (mean falls rate reduction of 58%) over the 17-month follow-up period. Strength and balance improved similarly in all groups over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 29 publications
8
128
1
2
Order By: Relevance
“…13 In nondrug studies, such as physical therapy interventions, it might take the form of a case series or a small trial with a short-term, physiological outcome, such as within-group changes in range of motion or strength, 1 rather than a patient-reported outcome such as a functional outcome questionnaire or recurrence, 5 or a surrogate outcome like a risk score shortly after intervention 7 rather than an observed, patientrelevant, longer-term outcome. 12 It may be reasonable to assess these aspects of treatment effect in the context of a feasibility study 2 ; however, the design of a full-size trial to assess either efficacy or effectiveness may still require a subsequent pilot study to get an indication of whether the intervention has promisingenough effects in longer-term, patientrelevant outcomes to warrant the time and expense of an RCT.…”
Section: Discussionmentioning
confidence: 99%
“…13 In nondrug studies, such as physical therapy interventions, it might take the form of a case series or a small trial with a short-term, physiological outcome, such as within-group changes in range of motion or strength, 1 rather than a patient-reported outcome such as a functional outcome questionnaire or recurrence, 5 or a surrogate outcome like a risk score shortly after intervention 7 rather than an observed, patientrelevant, longer-term outcome. 12 It may be reasonable to assess these aspects of treatment effect in the context of a feasibility study 2 ; however, the design of a full-size trial to assess either efficacy or effectiveness may still require a subsequent pilot study to get an indication of whether the intervention has promisingenough effects in longer-term, patientrelevant outcomes to warrant the time and expense of an RCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, several previous studies demonstrated positive effects of resistance training on these important resources of older adults (Barnett, Smith, Lord, Williams, Baumand, 2003;Clemson et al, 2012;Irez, Ozdemir, Evin, Irez, Korkusuz, 2011;Kaesler, Mellifont, Kelly, Taaffe, 2007;Krebs, Scarborough, McGibbon, 2007;Taylor et al, 2012). For fall prevention in particular, Training was separated into four periods (see Figure 1) with different configurations of training control.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size of the studies that were included in the present review was 171.8 -196.6 subjects (ranging from 9 16 to 684 subjects 38 ). The mean -standard deviation (SD) of the subjects' ages was 78.2 -5.3 (ranging from 70 -2 16 to 90 -2 35 ).…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…[23][24][25][26]30 Six studies investigated elderly aged 70 and older presenting recent history of injurious falls, transition for frailty, and recent illness-induced functional decline. 17,34,[37][38][39][40] Finally, one study investigated sarcopenic women presenting poor strength and gait ability levels based on literature criteria, 15 and one study investigated elderly aged 90 and older. 35 …”
Section: Subject Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation